Ectopic pelvic kidney in children - Miolski, Jelena; Marjanović, Jasminka; Jelena; Didić, Nevena; Zdravković, Vera (Medicinski časopis, 2023)
Introduction: An ectopic pelvic kidney is an anatomical anomaly in the position of the kidney. In the metanephros phase, its lifting and rotation from the pelvis in the sacral part of the spine to the lumbar region is absent. Due to vascular or other abnormalities, the kidney does not reach its usual anatomical position and therefore becomes ectopic. The position in which it can be placed is retroperitoneal, abdominal, thoracic with numerous variations. Case report: A three-month-old male infant underwent kidney screening during an ultrasound examination of the hips. There was a positive family history in the mother and maternal aunt of the existence of an ectopic, left pelvic kidney, without complications and accompanying symptoms. The infant’s clinical findings according to systems are normal, he is progressing in terms of body mass. Analyzes of urine, biochemistry and urine culture did not show any pathological findings. Ultrasound examination shows the left renal lobe completely filled with spleen, without visualization of the left kidney. In the right lumbar box, there is a right kidney, with regular dimensions, clear edges and normal thickness of the parenchyma. Inferior to the right kidney in the area of ​​the right lumbar region, facing inwards, there is a left kidney with regular ultrasonographic characteristics. Urinary bladder properly positioned, with normal dimensions and wall thickness. The infant was advised to see a pediatric nephrologist. Conclusion: The finding of an ectopic kidney in children is mostly asymptomatic. Neonatal ultrasound screening as a simple and inexpensive method in the first days of postnatal life is very important. It is necessary to pay special attention to possible associated anomalies, as well as to the possibility of eventual development of complications of an ectopic kidney, which is why patients should be advised to regularly follow up with a nephrologist. Key words: ectopic kidney, pelvic kidney, infant, child.